Endemic Bladder Stone Disease in Children, Pattern And Current Management: Experience From A Centre In Peri-Urban Setting In Pakistan - Mahar, Naveed; Soomro, Abdul Saboor; abbasi, Sammar Nissa; Hussain, Manzoor; Naqvi, Syed Anwer; Rizvi, Syed Adib (Urology Journal, 2024)
Purpose: To share our recent experience of the pattern and demography of endemic bladder calculi in children and the outcomes of current management strategies for the removal of bladder calculi in a peri-urban setting. Material and Methods: This retrospective longitudinal study was carried out at a dedicated urology centre. All patients with endemic bladder stones from January 2020 to December 2021 managed at our centre were included in this study. After discharge, each patient was followed up for 1 year. Data analysis was carried out with IBM SPSS v23. Mean and standard deviation were calculated for normally distributed continuous variables; for non-normally distributed continuous variables, median and IQR were calculated; frequency and percentage were calculated for categorical variables. Results: This study included 254 patients, with a male-to-female ratio of 10.5:1. The mean age of the patients was 4.80 ± 2.86 years. Ninety-one percent of the patients belonged to rural areas. Open cystolithotomy (OC) was performed in 11 (4.3%) patients, transurethral cystolithotripsy (TUCL) in 165 (65.0%), and percutaneous cystolithotomy (PCCL) in 78 (30.7%). The mean operative time was 48.8 ± 4.34 minutes for TUCL, 36.18 ± 7.4 minutes for open cystolithotomy, and 38.6 ± 5.2 minutes for PCCL. The most common stone composition was ammonium urate + calcium phosphate (33.1%). The complication rate was 4.8% in TUCL, 12.8% in PCCL, and 27.3% in open cystolithotomy. Stone clearance was 98.1% for TUCL and 100% for both PCCL and OC. Conclusion: Paediatric bladder calculus is still endemic in rural areas of Sindh with poor socioeconomic backgrounds. Timely diagnosis and early intervention with preventive measures can lead to better outcomes and fewer complications. Minimally invasive methods of cystolithotomy have a shorter hospital stay, are more cost-effective, and have fewer complications as compared to open cystolithotomy.